Kajian Literatur Efek Farmakologi Biji dan Buah Anggur (Vitis vinifera L.) - Kamilia Ayu Khairunnisa; Siti Hazar; Lanny Mulqie (UNISBA Press, 2022)
Abstract. Grapes are divided into two types that are commonly cultivated and can be consumed, namely Vitis vinifera and Vitis Labrusca. The vine (Vitis vinifera L) is one of the fruit plants with a high production rate, which has an important function in health. This study aims to determine the pharmacological potential of grape seeds and fruit from several research results and to find out what types of secondary metabolite compounds are contained in grape seeds and fruit. The research method used is SLR with two keywords using several databases. The results of the literature search showed pharmacological activities as antibacterial, antifungal, anticancer, antioxidant, and antihyperlipidemic. Antibacterial activity obtained from the inhibition zone produced strong activity, activity as antifungal obtained from the inhibition zone resulted in moderate activity, activity as a strong anticancer with an LC50 value produced with some cancer cells, activity as an antioxidant with an IC50 value of 11.3998 g/mL and activity as antihyperlipidemia obtained from a significant decrease in total cholesterol values. The secondary metabolite compounds contained in seeds and grapes are alkaloids, flavonoids, carotenoids, saponins, tannins and terpenoids. Abstrak. Tanaman anggur dibagi menjadi dua jenis yang umum dibudidayakan dan bisa dikonsumsi, yakni Vitis vinifera dan Vitis Labrusca. Tanaman anggur (Vitis vinifera L) merupakan salah satu tanaman yang buah dengan tingkat produksi yang tinggi, yang memiliki fungsi penting dalam kesehatan. Penelitian ini bertujuan untuk mengetahui potensi biji dan buah anggur secara farmakologi dari beberapa hasil penelitian dan mengetahui apa saja golongan senyawa metabolit sekunder yang terkandung dalam biji dan buah anggur. Metode penelitian yang digunakan adalah SLR dengan dua kata kunci menggunakan beberapa basis data. Hasil pencarian literatur menunjukkan aktivitas farmakologi sebagai antibakteri, antifungi, antikanker, antioksidan, dan antihiperlipidemia. Aktivitas antibakteri diperoleh dari zona hambat dihasilkan aktivitas yang kuat, aktivitas sebagai antifungi diperoleh dari zona hambat dihasilkan aktivitas yang sedang, aktivitas sebagai antikanker kuat dengan nilai LC50 yang dihasilkan dengan beberapa sel kanker, aktivitas sebagai antioksidan dengan nilai IC50 sebesar 11,3998 µg/mL dan aktivitas sebagai antihiperlipidemia diperoleh dari penurunan nilai kolesterol total yang signifikan. Golongan senyawa metabolit sekunder yang terkandung dalam biji dan buah anggur yaitu alkaloid, flavonoid, karotenoid, saponin, tanin dan terpenoid.